The smart senior care demand in China in the context of active ageing: a qualitative study with multiple perspectives - Huang, Qiyuan; Liu, Fang; Ge, Song; Teng, Shuang; Wu, Xiang; Zhang, Xiao; Qu, Zhe; Li, Ying; Wang, Aming; Li, Mei; Tang, Xianping (Frontiers in Public Health, 2025)
BackgroundWith the rapid population aging in China, smart senior care is urgently demanded. Therefore, it is necessary to comprehensively consider people’s demand for smart senior care for its better development. This study aimed to explore the needs and expectations of relevant stakeholders of smart senior care in China in the context of active aging.MethodsThis is a qualitative descriptive study, in which 21 semi-structured interviews were conducted between October 2021 and March 2022. A total of seven community-dwelling older adults, seven smart senior care managers, and seven providers were selected using purposeful sampling. Interviews were transcribed, translated into English, and analyzed by the thematic analysis method.ResultsFour major themes and 12 subcategories were identified in the data: “challenges of smart senior care” (low acceptance of users; high cost vs. low purchasing power; low coverage of smart devices and applications), “meet the demands of users” (strong medical care needs; meticulous life care needs; extensive social interaction needs), “multi-body participation” (online and offline integration; government’s broader role; cooperative gaming), and “all-around guarantee” (legal guarantee, technological empowerment, network security guarantee).ConclusionTo develop smart senior care in China in the context of active aging, it is essential to clarify the current issues and challenges faced by relevant stakeholders of smart senior care. To better develop smart senior care, we need to meet the health, life, and social care need of users, through multi-body participation and all-around guarantee.